The concept of life-creativity in modern psychology - DANYLIUK, Ivan; KOPYLOV, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The dynamics of modern socio-political life intensify psychological challenges, especially those related to personality functioning amid uncertainty and extended crisis. This increases the need for updated approaches to understanding life-meaning orientations, personal responsibility, and the processes of self-actualization and self-realization, particularly under martial law. In this context, the concept of life-creativity gains renewed importance in contemporary psychology. Methods. The study involved a review of theoretical and methodological literature. Methods of synthesis, comparison, and generalization were applied to define and interpret life-creativity across different psychological paradigms. Results. Interpretations of life-creativity differ depending on the theoretical perspective. In humanistic psychology (C. Rogers, A. Maslow), it is viewed as self-realization and the unfolding of one’s inner potential. The existential approach (R. May, V. Frankl) emphasizes creativity as a way of coping with existential crises and seeking life’s meaning. Behavioral theories (A. Bandura) explain it through environmental influence, modeling, and learning. In psychoanalysis (S. Freud, C. Jung, J. Lacan), life-creativity is a process of sublimation, resolving internal conflicts, and integrating the conscious and unconscious aspects of the mind. Ukrainian scholars (Y. Holovakha, N. Panina, T. Tytarenko, etc.) view the life path as a personal trajectory shaped by values, meaning, reflection, and activity. Life-creativity is seen as a means of adapting to crisis, forming life-meaning orientations, and actualizing personal potential. Conclusions. Life-creativity is an integrative psychological phenomenon that reflects active, value-based life construction in times of crisis. Across paradigms, it is associated with concepts such as subjectivity, self-realization, individuation, adaptation, and sublimation. Under martial law, studying it becomes particularly relevant, as individuals must adapt, reassess their priorities, and draw on inner resources to navigate ongoing change.